Carbon-supported multi-metal low-platinum core-shell structure catalyst as well as preparation method and application thereof

A carbon-supported multi-metal low-platinum core-shell structure catalyst addresses the limitations of platinum-based fuel cell catalysts by using a transition metal core and platinum shell, achieving high catalytic activity and durability with reduced platinum content and cost-effective synthesis.

CN119133486APending Publication Date: 2024-12-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310693669.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The high cost and instability of platinum-based catalysts in fuel cells due to low reserves and poor performance under high pressure and acidic conditions hinder their commercialization.

Method used

A carbon-supported multi-metal low-platinum core-shell structure catalyst is developed, where a transition metal or metal alloy serves as the core and platinum as the shell, synthesized through a method involving deionized water, microwave-assisted reduction, and ethylene glycol as a solvent to achieve a stable core-shell structure with low platinum loading.

Benefits of technology

The catalyst exhibits high catalytic activity, durability, and stability, reducing platinum usage while maintaining performance, and is cost-effective with an environmentally friendly synthesis process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133486A_ABST
    Figure CN119133486A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, in particular to a carbon-loaded multi-metal low-platinum core-shell structure catalyst and a preparation method and application thereof.The catalyst comprises carrier carbon and active components loaded on the surface of the carrier carbon, and the active components comprise platinum and transition metal; in the catalyst, based on the total weight of the catalyst, the content of the carrier carbon is 60.0 wt.%-80.0 wt.%; the content of platinum is 5.0 wt.% to 20.0 wt.%; the content of the transition metal is 10.0 wt.%-25.0 wt.%; the structure of the active component is a core-shell structure formed by transition metal and platinum, the transition metal or transition metal alloy is an inner core, and platinum is a shell layer; the transition metal in the transition metal or the transition metal alloy is selected from at least one of IB group metal, IIB group metal and VIII group metal. The catalyst provided by the invention has the advantages of stable core-shell structure, simple preparation, low platinum loading capacity, high catalytic activity, strong durability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a carbon-supported multi-metal low-platinum core-shell structure catalyst and a preparation method and application thereof. Background Art

[0002] The extensive use of fossil energy has caused serious environmental pollution and affected people's daily lives. Reducing the use of fossil energy and finding new clean energy and energy storage and conversion devices have become one of the hot issues in current research.

[0003] As an energy storage and conversion device, fuel cells can directly convert chemical energy into electrical energy, and have many advantages such as high conversion efficiency, high energy density, and no pollution to products. At present, the most widely used fuel cell catalyst is precious metal platinum (Pt), but metal Pt has low reserves and high prices. At the same time, it has poor stability under the high pressure and high acid environment of fuel cells, which limits the commercial development of fuel cells. Developing low-load, high-performance platinum-based catalysts is the key to promoting the commercialization of fuel cells.

[0004] In the process of catalyst development and preparation, using relatively cheap and abundant transition metals as the core, and loading a layer of Pt shell on its surface through chemical preparation methods to synthesize core-shell structure catalysts can greatly reduce the amount of Pt used, thereby reducing the cost of the catalyst. At the same time, since the lattice constant of the core metal is smaller than that of the shell Pt, compressive strain will be generated, causing the d-band center to move downward, reducing the activation energy of oxygen adsorption, thereby improving the catalytic performance of the catalyst.

[0005] Based on this background, the present application studies and develops a carbon-supported multi-metal low-platinum core-shell structure catalyst and a preparation method thereof. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a carbon-supported multi-metal low-platinum core-shell structure catalyst and a preparation method and application thereof. The catalyst has the advantages of a stable core-shell structure, simple preparation, low platinum loading, high catalytic activity and strong durability.

[0007] The first aspect of the present invention provides a carbon-supported multi-metal low-platinum core-shell structure catalyst, the catalyst comprising a carrier carbon and an active component supported on the surface of the carrier carbon, the active component comprising platinum and a transition metal;

[0008] In the catalyst, the content of the carrier carbon is 60.0wt.%-80.0wt.%, preferably 65.0wt.%-75.0wt.%, based on the total weight of the catalyst;

[0009] The content of platinum is 5.0wt.%-20.0wt.%, preferably 8.0wt.%-15.0wt.%;

[0010] The content of transition metal is 10.0wt.%-25.0wt.%, preferably 15.0wt.%-20.0wt.%;

[0011] The structure of the active component is a core-shell structure formed by transition metal and platinum, wherein the transition metal or transition metal alloy is the core and platinum is the shell;

[0012] The transition metal or the transition metal alloy is selected from at least one of Group IB, Group IIB, and Group VIII metals.

[0013] A second aspect of the present invention provides a method for preparing the above catalyst, the preparation method comprising the following steps:

[0014] (1) mixing and dispersing carbon powder, deionized water, and a transition metal precursor under stirring conditions to obtain a first mixed solution;

[0015] (2) drying and grinding the first mixed solution, and then reducing it under a reducing atmosphere to obtain a carbon-supported transition metal core or a carbon-supported transition metal alloy core;

[0016] (3) under stirring conditions, mixing and dispersing the carbon-supported transition metal core or the carbon-supported transition metal alloy core, the polyol, and the platinum salt precursor to obtain a second mixed solution;

[0017] (4) adjusting the second mixed solution to a weak alkaline state, stirring, and microwave heating to obtain a carbon-supported multi-metal low-platinum core-shell structure catalyst;

[0018] The transition metal in the transition metal precursor is selected from at least one of Group IB, Group IIB, and Group VIII metals;

[0019] The amount of each component used is such that the content of the carrier carbon in the catalyst is 60.0wt.%-80.0wt.%, preferably 65.0wt.%-75.0wt.%, based on the total weight of the catalyst;

[0020] The content of platinum is 5.0wt.%-20.0wt.%, preferably 8.0wt.%-15.0wt.%;

[0021] The content of transition metal is 10.0 wt.%-25.0 wt.%, preferably 15.0 wt.%-20.0 wt.%.

[0022] The third aspect of the present invention provides a carbon-supported multi-metal low-platinum core-shell structure catalyst prepared by the above-mentioned preparation method.

[0023] A fourth aspect of the present invention provides an application of the above-mentioned carbon-supported multi-metal low-platinum core-shell structure catalyst in a fuel cell.

[0024] The beneficial effects of the present invention are:

[0025] (1) The carbon-supported multi-metal low-platinum core-shell structure catalyst proposed in the present invention has a structurally stable core-shell structure, wherein the transition metal or transition metal alloy is the core and platinum is the shell. At the same time, the catalyst has the advantages of simple preparation, low platinum loading, high catalytic activity and strong durability.

[0026] (2) The method for preparing the carbon-supported multi-metal low-platinum core-shell structure catalyst proposed in the present invention uses deionized water as a solvent and hydrogen as a reducing agent, and obtains a metal core with a stable structure by adjusting the reaction temperature and reaction time.

[0027] (3) The method for preparing the carbon-supported multi-metal low-platinum core-shell structure catalyst proposed in the present invention adopts a microwave-assisted reduction method, with ethylene glycol as a solvent and a mixture of ethylene glycol and sodium borohydride as a reducing agent, to reduce the platinum layer to the metal core, thereby effectively preparing a core-shell structure catalyst with a certain atomic ratio and a small nanoparticle size.

[0028] (4) The method for preparing a carbon-supported multi-metal low-platinum core-shell structure catalyst proposed in the present invention synthesizes a carbon-supported multi-metal low-platinum core-shell structure catalyst with Pt as the shell and transition metal or transition metal alloy as the core by adjusting the temperature and time of the microwave reaction during the reaction process. The preparation process is simple and stable.

[0029] (5) The method for preparing the carbon-supported multi-metal low-platinum core-shell structure catalyst proposed in the present invention uses low-cost metal salts as reaction raw materials, which reduces the synthesis cost of the catalyst and is easy to scale up. At the same time, the process is environmentally friendly and will promote the further development of core-shell structure catalysts.

[0030] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention with reference to the accompanying drawings.

[0032] Figure 1 This is the XRD diagram of the carbon-supported multi-metal low-platinum core-shell structure catalyst (Co@Pt / C) obtained in step (5) of Example 1 of the present invention.

[0033] Figure 2-1This is a high-resolution electron microscope image of the carbon-supported multi-metal low-platinum core-shell structure catalyst (Co@Pt / C) obtained in step (5) of Example 1 of the present invention.

[0034] Figure 2-2 yes Figure 2-1 A partial enlarged view of . DETAILED DESCRIPTION

[0035] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0036] The present invention provides a carbon-supported multi-metal low-platinum core-shell structure catalyst, which comprises a carrier carbon and an active component supported on the surface of the carrier carbon, wherein the active component comprises platinum and a transition metal;

[0037] In the catalyst, the content of the carrier carbon is 60.0wt.%-80.0wt.%, preferably 65.0wt.%-75.0wt.%, based on the total weight of the catalyst;

[0038] The content of platinum is 5.0wt.%-20.0wt.%, preferably 8.0wt.%-15.0wt.%;

[0039] The content of transition metal is 10.0wt.%-25.0wt.%, preferably 15.0wt.%-20.0wt.%;

[0040] The structure of the active component is a core-shell structure formed by transition metal and platinum, wherein the transition metal or transition metal alloy is the core and platinum is the shell;

[0041] The transition metal is a single transition metal or a transition metal alloy, and is selected from at least one of Group IB, Group IIB, and Group VIII metals.

[0042] According to the present invention, the particle size of the active component is 5 to 10 nm.

[0043] According to the present invention, the carrier carbon is at least one of carbon black, carbon nanotubes, and graphene, preferably conductive carbon black, and more preferably XC-72 conductive carbon black.

[0044] Preferably, the transition metal is at least one of iron, cobalt, nickel, copper and zinc.

[0045] In the present invention, the carbon-supported multi-metal low-platinum core-shell structure catalyst has a structurally stable core-shell structure, wherein the transition metal or transition metal alloy is the core and platinum is the shell. At the same time, the catalyst has the advantages of simple preparation, low platinum loading, high catalytic activity and strong durability.

[0046] The present invention also provides a method for preparing the above catalyst, which comprises the following steps:

[0047] (1) mixing and dispersing carbon powder, deionized water, and a transition metal precursor under stirring conditions to obtain a first mixed solution;

[0048] (2) drying and grinding the first mixed solution, and then reducing it in a reducing atmosphere to obtain a carbon-supported transition metal core or a carbon-supported transition metal alloy core;

[0049] (3) mixing and dispersing the carbon-supported transition metal core or the carbon-supported transition metal alloy core, the polyol, and the platinum salt precursor under stirring conditions to obtain a second mixed solution;

[0050] (4) adjusting the second mixed solution to a weak alkaline state, stirring, and microwave heating to obtain a carbon-supported multi-metal low-platinum core-shell structure catalyst;

[0051] The transition metal in the transition metal precursor is a single transition metal or a transition metal alloy, selected from at least one of Group IB, Group IIB, and Group VIII metals; accordingly, the carbon-supported transition metal core formed in step (2) is a carbon-supported single transition metal core or a carbon-supported transition metal alloy core;

[0052] The amount of each component used is such that the content of the carrier carbon in the catalyst is 60.0wt.%-80.0wt.%, preferably 65.0wt.%-75.0wt.%, based on the total weight of the catalyst;

[0053] The content of platinum is 5.0wt.%-20.0wt.%, preferably 8.0wt.%-15.0wt.%;

[0054] The content of transition metal is 10.0 wt.%-25.0 wt.%, preferably 15.0 wt.%-20.0 wt.%.

[0055] According to the present invention, in step (1), the carbon powder is at least one of carbon black, carbon nanotubes, and graphene, preferably conductive carbon black, and more preferably XC-72 conductive carbon black;

[0056] The transition metal is at least one of iron, cobalt, nickel, copper and zinc;

[0057] The transition metal precursor is at least one of a nitrate, a sulfate, a halide, an amine complex, a hydrohalic acid or a hydrohalic acid salt of a transition metal;

[0058] For every 1 mg of carbon powder, the amount of deionized water added is 0.1-1 mL.

[0059] In the present invention, the preparation method of the carbon-supported multi-metal low-platinum core-shell structure catalyst uses deionized water as a solvent and hydrogen as a reducing agent, and obtains a metal core with a stable structure by adjusting the reaction temperature and reaction time.

[0060] In the present invention, a method for preparing a carbon-supported multi-metal low-platinum core-shell structure catalyst adopts a microwave-assisted reduction method, ethylene glycol is used as a solvent, and a mixed solution of ethylene glycol and sodium borohydride is used as a reducing agent to reduce the platinum layer to the metal core, thereby effectively preparing a core-shell structure catalyst with a certain atomic ratio and a small nanoparticle size.

[0061] Preferably, in step (1), the dispersion is carried out by ultrasonic dispersion, the temperature of ultrasonic dispersion is 20-30° C., and the time is 1 to 1.5 h;

[0062] The stirring time is 5 to 10 minutes.

[0063] According to the present invention, in step (2), the drying temperature is 70-90°C and the drying time is 16-20h;

[0064] The reducing atmosphere is a mixed atmosphere of hydrogen and argon, wherein the volume percentage of hydrogen is 2-8% and the volume percentage of argon is 92-98%;

[0065] The reduction temperature is 250-350°C and the time is 2-4 hours.

[0066] According to the present invention, in step (3), dispersion is carried out by ultrasonic dispersion, the temperature of ultrasonic dispersion is 20-30° C., and the time is 1 to 1.5 h;

[0067] The stirring time is 2 to 8 minutes;

[0068] The platinum salt precursor is at least one of chloroplatinic acid, chloroplatinic acid, chloroplatinic acid, potassium chloroplatinate, ammonium chloroplatinate, platinum acetylacetonate, and platinum acetylacetonate;

[0069] For every 1 mg of carbon powder, the amount of polyol added is 0.1-1 mL;

[0070] The polyol is at least one of ethylene glycol, glycerol, butanediol and pentaerythritol.

[0071] Preferably, in step (4), an alkaline solution is added to adjust the second mixed solution to a weak alkalinity, wherein the weak alkalinity is pH 7.5-8.5, and the alkaline solution is preferably a sodium hydroxide solution;

[0072] The power of microwave heating is 200-400W, the temperature is 70-90°C, and the time is 20-40min.

[0073] In the present invention, a method for preparing a carbon-supported multi-metal low-platinum core-shell structure catalyst is provided. During the reaction process, the temperature and time of the microwave reaction are adjusted to synthesize a carbon-supported multi-metal low-platinum core-shell structure catalyst with Pt as the shell and a transition metal or a transition metal alloy as the core. The preparation process is simple and stable.

[0074] In the present invention, the preparation method of the carbon-supported multi-metal low-platinum core-shell structure catalyst uses low-cost metal salts as reaction raw materials, which reduces the synthesis cost of the catalyst and is easy to scale up. At the same time, the process is environmentally friendly and will promote the further development of core-shell structure catalysts.

[0075] The present invention also provides a carbon-supported multi-metal low-platinum core-shell structure catalyst prepared by the above preparation method.

[0076] The present invention also provides the use of the above-mentioned carbon-supported multi-metal low-platinum core-shell structure catalyst in a fuel cell.

[0077] The present invention is further described below in conjunction with embodiments, but the scope of the present invention is not limited to these embodiments.

[0078] In the following examples, Examples 1-9 are examples of carbon-supported multi-metal low-platinum core-shell structure catalysts, and Comparative Examples 1-2 are comparative examples of carbon-supported multi-metal low-platinum core-shell structure catalysts.

[0079] Example 1

[0080] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 80.65 mg of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0081] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0082] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0083] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0084] (5) Under stirring, add 37.95 mg of chloroplatinic acid (H2PtCl6·6H2O) to the mixed solution obtained in step (4) to obtain a mixed solution;

[0085] (6) To the mixed solution obtained in step (5), sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8, and then the system was heated to 80° C. by a microwave reactor with a power of 300 W under stirring conditions, and the reaction was continued for 30 minutes to obtain a carbon-supported platinum-cobalt low-platinum core-shell structure catalyst S1, in which the mass percentages of carbon, platinum and cobalt in S1 were 70:12.5:17.5.

[0086] Example 2

[0087] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 80.65 mg of nickel dichloride hexahydrate (NiCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0088] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0089] (3) placing the powder obtained in step (2) in a porcelain boat, reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported nickel metal (Ni / C);

[0090] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0091] (5) Under stirring, add 37.95 mg of chloroplatinic acid (H2PtCl6·6H2O) to the mixed solution obtained in step (4) to obtain a mixed solution;

[0092] (6) To the mixed solution obtained in step (5), sodium hydroxide solution is added dropwise to adjust the pH value of the solution to 8, and then the system is heated to 80° C. by a microwave reactor with a power of 300 W under stirring conditions, and the reaction is continued for 30 minutes to obtain a carbon-supported platinum-nickel low-platinum core-shell structure catalyst S2, in which the mass percentages of carbon, platinum and nickel are 70:12.5:17.5.

[0093] Example 3

[0094] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 52.92 mg of zinc chloride dihydrate (ZnCl2·2H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0095] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0096] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported zinc metal (Zn / C);

[0097] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0098] (5) Under stirring, add 37.95 mg of chloroplatinic acid (H2PtCl6·6H2O) to the mixed solution obtained in step (4) to obtain a mixed solution;

[0099] (6) To the mixed solution obtained in step (5), sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8, and then the system was heated to 80° C. by a microwave reactor with a power of 300 W under stirring conditions, and the reaction was continued for 30 minutes to obtain a carbon-supported platinum-zinc low-platinum core-shell structure catalyst S3, in which the mass percentages of carbon, platinum and zinc were 70:12.5:17.5.

[0100] Example 4

[0101] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 138.28 of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 70:30;

[0102] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0103] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0104] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0105] (5) Under stirring, add 37.95 mg of chloroplatinic acid (H2PtCl6·6H2O) to the mixed solution obtained in step (4) to obtain a mixed solution;

[0106] (6) To the mixed solution obtained in step (5), sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8, and then the system was heated to 80° C. in a microwave reactor at a power of 300 W under stirring conditions, and the reaction was continued for 30 minutes to obtain a carbon-supported platinum-cobalt low-platinum core-shell structure catalyst S4, in which the mass percentages of carbon, platinum and cobalt were 62.2:11.1:26.7.

[0107] Example 5

[0108] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 107.55 g of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 75:25;

[0109] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0110] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0111] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0112] (5) Under stirring, add 37.95 mg of chloroplatinic acid (H2PtCl6·6H2O) to the mixed solution obtained in step (4) to obtain a mixed solution;

[0113] (6) To the mixed solution obtained in step (5), sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8, and then the system was heated to 80° C. in a microwave reactor at a power of 300 W under stirring conditions, and the reaction was continued for 30 minutes to obtain a carbon-supported platinum-cobalt low-platinum core-shell structure catalyst S5, in which the mass percentages of carbon, platinum and cobalt were 66.1:11.8:22.1.

[0114] Example 6

[0115] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 80.65 mg of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0116] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0117] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0118] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0119] (5) Under stirring, 47.82 mg of chloroplatinic acid (H2PtCl6·6H2O) was added to the mixed solution obtained in step (4) to obtain a mixed solution;

[0120] (6) To the mixed solution obtained in step (5), sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8, and then the system was heated to 80° C. in a microwave reactor at a power of 300 W under stirring conditions, and the reaction was continued for 30 minutes to obtain a carbon-supported platinum-cobalt low-platinum core-shell structure catalyst S6, in which the mass percentages of carbon, platinum and cobalt were 67.8:15.3:16.9.

[0121] Example 7

[0122] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 80.65 mg of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0123] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0124] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0125] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0126] (5) Under stirring, 31.88 mg of chloroplatinic acid (H2PtCl6·6H2O) was added to the mixed solution obtained in step (4) to obtain a mixed solution;

[0127] (6) To the mixed solution obtained in step (5), sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8, and then the system was heated to 80° C. by a microwave reactor with a power of 300 W under stirring, and the reaction was continued for 30 minutes to obtain a carbon-supported platinum-cobalt low-platinum core-shell structure catalyst S7, in which the mass percentages of carbon, platinum and cobalt in S7 were 71.4:10.7:17.9.

[0128] Example 8

[0129] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 80.65 mg of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0130] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0131] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0132] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0133] (5) Under stirring, add 37.95 mg of chloroplatinic acid (H2PtCl6·6H2O) to the mixed solution obtained in step (4) to obtain a mixed solution;

[0134] (6) To the mixed solution obtained in step (5), sodium hydroxide solution is added dropwise to adjust the pH value of the solution to 8, and then the system is heated to 80° C. in a microwave reactor at a power of 200 W under stirring conditions, and the reaction is continued for 30 minutes to obtain a carbon-supported platinum-cobalt low-platinum core-shell structure catalyst S8, in which the mass percentages of carbon, platinum and cobalt are 70:12.5:17.5.

[0135] Example 9

[0136] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 80.65 mg of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0137] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0138] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0139] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0140] (5) Under stirring, add 37.95 mg of chloroplatinic acid (H2PtCl6·6H2O) to the mixed solution obtained in step (4) to obtain a mixed solution;

[0141] (6) To the mixed solution obtained in step (5), sodium hydroxide solution is added dropwise to adjust the pH value of the solution to 8, and then the system is heated to 80° C. in a microwave reactor at a power of 400 W under stirring conditions, and the reaction is continued for 30 minutes to obtain a carbon-supported platinum-cobalt low-platinum core-shell structure catalyst S9, in which the mass percentages of carbon, platinum and cobalt are 70:12.5:17.5.

[0142] Comparative Example 1

[0143] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 80.65 mg of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0144] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0145] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0146] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0147] (5) To the mixed solution obtained in step (4), sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8, and then the system was heated to 80° C. by a microwave reactor with a power of 300 W under stirring conditions, and the reaction was continued for 30 minutes to obtain a carbon-supported cobalt core structure catalyst D1, in which the mass percentage of carbon and cobalt in D1 was 80:20.

[0148] Comparative Example 2

[0149] (1) 80 mg of XC-72 conductive carbon black was weighed and placed in a beaker, 15 ml of deionized water was added, and the XC-72 conductive carbon black was uniformly dispersed in the water at room temperature, and then magnetically stirred for 8 minutes, 80.65 mg of cobalt chloride hexahydrate (CoCl2·6H2O) was added, and ultrasonic dispersion was performed for 1 hour to mix the mixture uniformly to obtain a mixed solution, in which the mass percentage of carbon and cobalt ions in the mixed solution was 80:20;

[0150] (2) drying the mixed solution of step (1) in an oven at 80° C. for 18 h, evaporating the water in the solution, and then grinding it into a powder using a mortar;

[0151] (3) placing the powder obtained in step (2) in a porcelain boat, and reducing it in a tube furnace at 300° C. for 3 h in a mixed gas atmosphere of 5% H2 / 95% Ar to obtain carbon-supported cobalt metal (Co / C);

[0152] (4) placing the carbon-supported cobalt-copper alloy obtained in step (3) in a three-necked flask, adding 40 mL of ethylene glycol, ultrasonically dispersing at room temperature for 1 h, and magnetically stirring for 5 min to obtain a mixed solution;

[0153] (5) Under stirring, add 37.95 mg of chloroplatinic acid (H2PtCl6·6H2O) to the mixed solution obtained in step (4) to obtain a mixed solution;

[0154] (6) To the mixed solution obtained in step (5), sodium hydroxide solution was added dropwise to adjust the pH value of the solution to 8, and then the system was heated to 80° C. by a microwave reactor under stirring conditions, and the reaction was continued for 30 minutes to obtain a carbon-supported platinum-cobalt low-platinum core-shell structure catalyst D2, wherein the mass percentages of carbon, platinum and cobalt in D2 were 70:12.5:17.5.

[0155] Test Example 1

[0156] 10 mg of catalysts S1-S9 in the examples and catalysts D1-D2 in the comparative examples were used to obtain different catalyst evaluation results, as shown in Table 1.

[0157] Table 1 Evaluation results of catalysts

[0158]

[0159] By comparing the data in Table 1, it can be seen that the catalytic activity of the catalyst can be improved by using microwave heating and coating the core with a Pt shell, and the best catalytic activity is obtained when the mass percentage of carbon, platinum and cobalt added is 70:12.5:17.5. Changing the power of microwave heating has little effect on the catalyst activity.

[0160] Test Example 2

[0161] The carbon-supported platinum-cobalt low-platinum core-shell structure catalyst (Co@Pt / C) obtained in step (6) of Example 1 of the present invention was subjected to X-ray diffraction to analyze its diffraction pattern.

[0162] like Figure 1As shown, it is the XRD pattern of the carbon-supported platinum cobalt low-platinum core-shell structure catalyst (Co@Pt / C) obtained in step (6) of Example 1 of the present invention, and the broad peak at 2θ=25° corresponds to the peak of the carbon support. The characteristic diffraction peaks of the Pt shell at about 2θ=39.8°, 46.9°, 67.8° and 81.3° are attributed to the Pt face-centered cubic structure crystal planes (111), (200), (220) and (311), indicating that the surface of the synthesized catalyst is a characteristic structure of Pt.

[0163] By characterizing the structure of the product prepared in Example 1, the carbon-supported platinum-cobalt low-platinum core-shell structure catalyst (Co@Pt / C) was proved to be a carbon carrier with active components loaded on the carbon surface, wherein the active component is a platinum-cobalt low-platinum core-shell structure catalyst (Co@Pt / C) with a particle size of 5 to 10 nm. Electron microscopy observation showed that the distribution was uniform.

[0164] Test Example 3

[0165] The carbon-supported platinum-cobalt low-platinum core-shell structure catalyst (Co@Pt / C) obtained in step (6) of Example 1 of the present invention was analyzed by electron microscopy.

[0166] like Figure 2-1 As shown, it is a high-resolution electron micrograph of the carbon-supported platinum-cobalt low-platinum core-shell structure catalyst (Co@Pt / C) obtained in step (6) of Example 1 of the present invention. Analysis shows that the active ingredient has good dispersion on the carbon carrier, and the particles are relatively uniform, with a particle size of about 5 nm; there is only a small amount of agglomeration. Figure 2-2 yes Figure 2-1 A partial enlarged view of .

[0167] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

[0168] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A carbon-supported multi-metal low-platinum core-shell catalyst, It is characterized in that The catalyst comprises a carrier carbon and an active component loaded on the surface of the carrier carbon, wherein the active component comprises platinum and a transition metal; In the catalyst, the content of the carrier carbon is 60.0wt.%-80.0wt.%, preferably 65.0wt.%-75.0wt.%, based on the total weight of the catalyst; The content of platinum is 5.0wt.%-20.0wt.%, preferably 8.0wt.%-15.0wt.%; The content of transition metal is 10.0wt.%-25.0wt.%, preferably 15.0wt.%-20.0wt.%; The structure of the active component is a core-shell structure formed by transition metal and platinum, wherein the transition metal is the core and platinum is the shell; The transition metal is a single transition metal or a transition metal alloy, and is selected from at least one of Group IB, Group IIB, and Group VIII metals.

2. The catalyst according to claim 1, It is characterized in that The particle size of the active component is 5 to 10 nm.

3. The catalyst according to claim 1, It is characterized in that The carrier carbon is at least one of carbon black, carbon nanotubes, and graphene, preferably conductive carbon black, and more preferably XC-72 conductive carbon black.

4. The catalyst according to claim 1, It is characterized in that The transition metal is at least one of iron, cobalt, nickel, copper and zinc.

5. A method for preparing a carbon-supported multi-metal low-platinum core-shell structure catalyst, It is characterized in that The preparation method comprises the following steps: (1) mixing and dispersing carbon powder, deionized water, and a transition metal precursor under stirring conditions to obtain a first mixed solution; (2) drying and grinding the first mixed solution, and then reducing it in a reducing atmosphere to obtain a carbon-supported transition metal core; (3) under stirring conditions, mixing and dispersing the carbon-supported transition metal core, polyol, and platinum salt precursor to obtain a second mixed solution; (4) adjusting the second mixed solution to a weak alkaline state, stirring, and microwave heating to obtain a carbon-supported multi-metal low-platinum core-shell structure catalyst; The transition metal in the transition metal precursor is a single transition metal or a transition metal alloy, selected from at least one of Group IB, Group IIB, and Group VIII metals; The amount of each component used is such that the content of the carrier carbon in the catalyst is 60.0wt.%-80.0wt.%, preferably 65.0wt.%-75.0wt.%, based on the total weight of the catalyst; The content of platinum is 5.0wt.%-20.0wt.%, preferably 8.0wt.%-15.0wt.%; The content of transition metal is 10.0 wt.%-25.0 wt.%, preferably 15.0 wt.%-20.0 wt.%.

6. The preparation method according to claim 5, It is characterized in that In step (1), the carbon powder is at least one of carbon black, carbon nanotubes, and graphene, preferably conductive carbon black, more preferably XC-72 conductive carbon black; The transition metal is at least one of iron, cobalt, nickel, copper and zinc; The transition metal precursor is at least one of a nitrate, a sulfate, a halide, an amine complex, a hydrohalic acid, and a hydrohalic acid salt of a transition metal; For every 1 mg of carbon powder, the amount of deionized water added is 0.1-1 mL.

7. The preparation method according to claim 5, It is characterized in that In step (1), the dispersion is carried out by ultrasonic dispersion, the temperature of the ultrasonic dispersion is 20-30° C., and the time is 1-1.5 h; The stirring time is 5 to 10 minutes.

8. The preparation method according to claim 5, It is characterized in that In step (2), the drying temperature is 70-90° C. and the drying time is 16-20 h; The reducing atmosphere is a mixed atmosphere of hydrogen and argon, wherein the volume percentage of hydrogen is 2-8% and the volume percentage of argon is 92-98%; The reduction temperature is 250-350° C. and the time is 2-4 hours.

9. The preparation method according to claim 5, It is characterized in that In step (3), the dispersion is carried out by ultrasonic dispersion, the temperature of the ultrasonic dispersion is 20-30° C., and the time is 1 to 1.5 h; The stirring time is 2 to 8 minutes; The platinum salt precursor is at least one of chloroplatinic acid, chloroplatinic acid, potassium chloroplatinate, ammonium chloroplatinate, platinum acetylacetonate, and platinum acetylacetonate; For every 1 mg of carbon powder, the amount of polyol added is 0.1-1 mL; The polyol is at least one of ethylene glycol, propylene glycol, butylene glycol and pentaerythritol.

10. The preparation method according to claim 5, It is characterized in that In step (4), an alkaline solution is added to adjust the second mixed solution to a weak alkalinity, wherein the weak alkalinity is pH 7.5-8.5, and the alkaline solution is preferably a sodium hydroxide solution; The microwave heating has a power of 200-400W, a temperature of 70-90°C and a time of 20-40min.

11. A carbon-supported multi-metal low-platinum core-shell structure catalyst prepared by the preparation method according to any one of claims 5 to 10.

12. Use of the carbon-supported multi-metal low-platinum core-shell structure catalyst according to any one of claims 1 to 4 and 11 in a fuel cell.